LINGUISTIC FEATURES OF CHILDREN'S LEXICON IN GERMAN AND UZBEK LANGUAGES (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article provides information about the linguistic features of children's lexicon in German and Uzbek languages. The article presents the grammatical features of the language, types of words, the use of compound words, features of possession, and historical and cultural foundations. This article is intended to be useful for language learners and linguists.